(untitled) (Research, Society and Development, 2022)
Objective: To analyze the mental health of health professionals at risk of domestic violence in primary care in the municipality of João Pessoa in the context of the pandemic. Methods: Descriptive, cross-sectional study with quantitative approach. The sample was probabilistic and clustered with 64 randomly selected female professionals. These health professionals were interviewed through two structured instruments in the form of a questionnaire that proposed the screening of mental suffering and identification of the risk of suffering domestic violence, respectively. The study was conducted in 33 Family Health Units in September 2021. Results: 70.32% of the health professionals fit into the category of medium risk for domestic violence and 50% showed signs of mental distress. The general profile of the professionals involved women with depressive-anxious mood, depressive thoughts, somatic symptoms, decreased vital energy and negative evaluation of themselves. However, no suicidal ideas, loss of interest and appetite were observed, characteristics commonly found in the mood described. Conclusion: COVID-19 negatively impacted the mental health of professionals at risk of domestic violence. Many of them, in addition to work overload, still deal with violence in the family context, which substantially influences their mental health.